Apolipoprotein A4 Defines the Villus-Crypt Border in Duodenal Specimens for Celiac Disease Morphometry - Taavela, Juha; Viiri, Keijo; Välimäki, Anna; Sarin, Jani; Salonoja, Kristiina; Mäki, Markku; Isola, Jorma (Frontiers in Immunology, 2021)
Histological evaluation of the small intestinal mucosa is the cornerstone of celiac disease diagnostics and an important outcome in scientific studies. Gluten-dependent injury can be evaluated either with quantitative morphometry or grouped classifications. A drawback of mucosal readings is the subjective assessment of the border where the crypt epithelium changes to the differentiated villus epithelium. We studied potential immunohistochemical markers for the detection of the villus-crypt border: apolipoprotein A4 (APOA4), Ki-67, glucose transporter 2, keratin 20, cytochrome P450 3A4 and intestinal fatty-acid binding protein. Among these, villus-specific APOA4 was chosen as the best candidate for further studies. Hematoxylin-eosin (H&E)- and APOA4 stained duodenal biopsy specimens from 74 adult patients were evaluated by five observers to determine the villus-to-crypt ratio (VH:CrD). APOA4 delineated the villus to crypt epithelium transition clearly, and the correlation coefficient of VH:CrD values between APOA4 and H&E was excellent (r=0.962). The VH:CrD values were lower in APOA4 staining (p<0.001) and a conversion factor of 0.2 in VH:CrD measurements was observed to make the two methods comparable to each other. In the intraobserver analysis, the doubled standard deviations, representing the error ranges, were 0.528 for H&E and 0.388 for APOA4 staining, and the ICCs were 0.980 and 0.971, respectively. In the interobserver analysis, the average error ranges were 1.017 for H&E and 0.847 for APOA4 staining, and the ICCs were better for APOA4 than for H&E staining in all analyses. In conclusion, the reliability and reproducibility of morphometrical VH:CrD readings are improved with the use of APOA4 staining.